2012
DOI: 10.1111/j.1365-2427.2012.02857.x
|View full text |Cite
|
Sign up to set email alerts
|

Using palaeolimnological and limnological data to reconstruct the recent history of European lake ecosystems: introduction

Abstract: Summary 1. As future climate change is expected to have a major impact on freshwater lake ecosystems, it is important to assess the extent to which changes taking place in freshwater lakes can be attributed to the degree of climate change that has already taken place. 2. To address this issue, it is necessary to examine evidence spanning many decades by combining long‐term observational data sets and palaeolimnological records. 3. Here, we introduce a series of case studies of seven European lakes for which bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…This was also observed for 143 eutrophic and hypereutrophic lakes in South America, indicating that in systems characterized by high biovolume, the interaction of light availability with temperature and nutrients was the main driver of phytoplankton (Kosten et al 2012). This was confirmed by other studies conducted in eutrophic systems either using modeling (Elliott et al 2006;Elliott and May 2008) or monitoring data (Jö hnk et al 2008;Blank et al 2009). …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…This was also observed for 143 eutrophic and hypereutrophic lakes in South America, indicating that in systems characterized by high biovolume, the interaction of light availability with temperature and nutrients was the main driver of phytoplankton (Kosten et al 2012). This was confirmed by other studies conducted in eutrophic systems either using modeling (Elliott et al 2006;Elliott and May 2008) or monitoring data (Jö hnk et al 2008;Blank et al 2009). …”
Section: Discussionsupporting
confidence: 85%
“…Nutrients (i.e., either TN or TP, or both) in isolation were found to be solely responsible for changes in cyanobacteria in 8 of the 35 studies (23%) (Battarbee and Bennion 2012;Feuchtmayr et al 2012). Of those eight studies, four were conducted in microcosms or mesocosms with eutrophic conditions ( Moss et al 2003;Christoffersen et al 2006;Feuchtmayr et al 2010), three were conducted in eutrophic and mesotrophic lakes (Elliott 2010;Battarbee and Bennion 2012;Feuchtmayr et al 2012), and one in a hyper-eutrophic system (Eilers et al 2004). Only three studies found that other factors (e.g., zooplankton, macrophytes) were most responsible for driving variation in cyanobacterial biomass (Ruggiu et al 1998;Genkai-Kato and Carpenter 2005;Loverde-Oliveira et al 2009).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This is not surprising given that for some MS river basin management was a new departure, but it is also a reflection of the difficulties in restoring aquatic systems and similar problems have been reported from North America (George and Boyd, 2007). For lakes, recovery times can extend over at least 15 years (Battarbee and Bennion, 2012;Carvalho et al, 2012;Hobaek et al, 2012;Jeppesen et al, 2005), often caused by internal nutrient load and/or long retention times Søndergaard et al, 2007). The WFD recognises that in such situations achieving good status may take more time and it allows MS to extend deadlines for the achievement of good status on the basis of the natural conditions of the water body.…”
Section: What Happens Next?mentioning
confidence: 78%
“…Hence, sedimentary research plays a key role in deciphering the effects of increasing environmental pressure on aquatic ecosystems as sediments collect and unify environmental signals of both local and regional change (e.g. Cohen 2003;Battarbee and Bennion 2012). Understanding the variation in lake ecosystems, be it as a result of natural or anthropogenic causes, is of utmost importance if we are to fully comprehend how these ecosystems function and how they can be restored and protected (Smol 2002;Sayer et al 2010).…”
Section: Introductionmentioning
confidence: 98%